1997
DOI: 10.1002/pen.11828
|View full text |Cite
|
Sign up to set email alerts
|

Studies of post drawing relaxation phenomena in poly(ethylene terephthalate) by infrared spectroscopy

Abstract: In this paper, we study the relaxation behavior of initially amorphous poly(ethylene terephthalate) (PET) films drawn, at 80°C using a draw rate of 2 cm/min, to a draw ratio (A) from 1 to 5 and then quenched to room temperature. These films were then heated at different temperatures from 68 to 80°C for different times and their orientation determined. The orientation measurements were performed by transmission infrared spectroscopy and the bands used for the determination of orientation were those at 1340 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
(10 reference statements)
1
24
0
Order By: Relevance
“…Using this approach, several authors 15,16,23 have suggested that PET behaves as a rubber-like network when deformed at low to moderate draw ratios (λ ≤ 2.5), where PET will follow the Gaussian network model which predicts an increasing slope in the orientation function plotted as a function of λ, as given by Treloar: 21…”
Section: ■ Introductionmentioning
confidence: 98%
“…Using this approach, several authors 15,16,23 have suggested that PET behaves as a rubber-like network when deformed at low to moderate draw ratios (λ ≤ 2.5), where PET will follow the Gaussian network model which predicts an increasing slope in the orientation function plotted as a function of λ, as given by Treloar: 21…”
Section: ■ Introductionmentioning
confidence: 98%
“…Furthermore, the estimated draw ratio of 3.8 is higher than the critical value of around 2.2-2.5 required to generate shear-induced crystallization and inhibit molecular relaxation during the cooling phase. 8,15 Thus, the points generally tend toward the transverse apex, with f cT lying between 0.3 and 0.5, whereas the values of f cM and f cN are negative. As was observed for the type I bottles, for some points the value of f cN is not the lowest of the three, and this suggests a certain preference of the chains for the thickness direction.…”
Section: Effect Of the Mold Temperaturementioning
confidence: 97%
“…One way of alleviating this problem is to increase the crystallinity of the polymer during processing. 8 It is clear that if plastics are to compete successfully with glass, all the aforementioned properties must be optimized, and this means that it is important to characterize the morphology and to understand how it varies as a function of the processing conditions. Information can be obtained by means of various techniques, including birefringence, X-ray diffraction, heat-shrinkage measurements, differential scanning calorimetry, and infrared (IR) and Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…These two bands have been assigned to the CH 2 rocking of glycol [19e22]. The trans conformation can be present in both crystalline and amorphous phases [23], but the gauche conformation is found only in the amorphous phase [24]. The increase in the amount of the trans conformation can be attributed to a morphological change from a folded chain to an extended chain.…”
Section: Relationship Between Superstructure Of Nanofiber Sheet and Dmentioning
confidence: 98%